TATA KELOLA ENTREPRENEUR: ALTERNATIF PENGEMBANGAN MADRASAH FREE COST DAN MANDIRI DI MTS NEGERI 3 PAMEKASAN - Dr. Mohammad Holis (Madaris: Jurnal Guru Inovatif, 2021)
Implementation and outcome of entrepreneurial governance; alternative development of a free and independent cost madrasa in MTs Negeri 3 Pamekasan in empowering all potentials in the Madrasah environment and the community around Madrasah with target achievements: first, the actualization of morals to God, fellow humans, and the natural surroundings. Second, improve student learning achievement both academic and non academic. Third, entrepreneurial governance; as an alternative to the development of free cost madrasah. Fourth, making madrasa a place for learning without being shackled by social and economic stratification because of free cost education with guaranteed continuity of good learning and glorious achievement. Strategic steps taken by MTs Negeri 3 Pamekasan in realizing Entrepreneur Governance; Alternative Development of Madrasah Free Cost and independent in MTs Negeri 3 Pamekasan is to utilize the potential of pocket money brought by students to madrasah, and to promote Madrasah literacy products.